PELATIHAN DARING CARA EDIT VIDEO MUDAH DAN MENARIK UNTUK MEMAKSIMALKAN PEMBELAJARAN SISWA TINGKAT PRE-SCHOOL - Defriani, Meriska; Gito Resmi, Mochzen; Irmayanti, Dede (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
Sekolah Alam Purwakarta (SAP) is a school that integrates the pillars of faith, knowledge, leadership, and entrepreneurship. In the teaching and learning process, SAP not only emphasizes the achievement of academic goals but also on the development of life skills. In addition, SAP uses a national curriculum which is developed so that the universe and local potentials become learning resources, learning media, and classrooms. During the Covid-19 pandemic, almost all pre-school level student learning was carried out at home with guidance in the form of assignments prepared by the facilitator. Each task given aims to develop students' cognitive, motoric, or affective. In order to achieve this goal, each given task needs to be accompanied by a good explanation. This explanation can be presented using video. In addition, every task that has been done must be submitted by the parents to the facilitator as a daily assessment. To get good documentation, parents can use photos or videos as a medium. Based on this explanation, a video editing training needs to be carried out to maximize the teaching and learning process. This activity is carried out by providing online training to facilitators and parents of pre-school level students at SAP. This training was held for 120 minutes and was attended by 8 facilitators and 20 parents of students. With the implementation of this training, facilitators and parents of students have the ability to edit video so that they can maximize pre-school level student learning at SAP